The Crime of Aggression in the Rome Statute of the International Criminal Court - Burneo Labrín, José Antonio (2018)
In December of 2017, within the framework of the Rome Statute that creates the International Criminal Court, the 16th Assembly of States Parties adopted by consensus the Resolution ICC-ASP / 16 / Res.5, entitled «Activation of the jurisdiction of the Court over the crime of aggression». Under the aforementioned Resolution, it was established: (i) the definition of the crime of aggression adopted in 2010 by the Conference of States Parties to the Rome  Statute, held in Kampala (Uganda) has become applicable. Likewise, the universal scope of the criminal sanction of this crime is reaffirmed, by virtue of non-conventional international legal norms, like customary norms or jus cogens, and (ii) effective jurisdiction is granted to a jurisdictional body, the International Criminal Court, in order to administer justice with respect to the crime of aggression. In this paper it will be addressed the question of the definition of the crime of aggression under the Statute of Rome and its universal impact (Section I) and, then, the question of the jurisdiction of the International Criminal Court on this crime (Section II).